Mapping of the World Health Organization's Disability Assessment Schedule 2.0 to disability weights using the Multi‐Country Survey Study on Health and Responsiveness - Lokkerbol, Joran; Wijnen, Ben F. M.; Chatterji, Somnath; Kessler, Ronald C.; Chisholm, Dan (International journal of methods in psychiatric research, 2021)
Objectives To develop and test an internationally applicable mapping function for converting WHODAS‐2.0 scores to disability weights, thereby enabling WHODAS‐2.0 to be used in cost‐utility analyses and sectoral decision‐making. Methods Data from 14 countries were used from the WHO Multi‐Country Survey Study on Health and Responsiveness, administered among nationally representative samples of respondents aged 18+ years who were non‐institutionalized and living in private households. For the combined total of 92,006 respondents, available WHODAS‐2.0 items (for both 36‐item and 12‐item versions) were mapped onto disability weight estimates using a machine learning approach, whereby data were split into separate training and test sets; cross‐validation was used to compare the performance of different regression and penalized regression models. Sensitivity analyses considered different imputation strategies and compared overall model performance with that of country‐specific models. Results Mapping functions converted WHODAS‐2.0 scores into disability weights; R‐squared values of 0.700–0.754 were obtained for the test data set. Penalized regression models reached comparable performance to standard regression models but with fewer predictors. Imputation had little impact on model performance. Model performance of the generic model on country‐specific test sets was comparable to model performance of country‐specific models. Conclusions Disability weights can be generated with good accuracy using WHODAS 2.0 scores, including in national settings where health state valuations are not directly available, which signifies the utility of WHODAS as an outcome measure in evaluative studies that express intervention benefits in terms of QALYs gained.